The promotion of the good intercultural speaker through intercultural contacts in a Tunisian EFL textbook. (2nd January 2020) - Abid, Nadia; Moalla, Asma
ABSTRACT: This paper evaluates the potential of intercultural contacts portrayed in the content and tasks of a Tunisian EFL textbook for third-year secondary school students to develop the model of the intercultural speaker. The quantitative and qualitative analyses of the elements of intercultural contacts reveal that this portrayal is imbalanced in terms of frequency and variety and that their potential to help participants become good intercultural speakers is low. To compete with other sources of intercultural contacts, the textbook should include more frequent and varied contact situations where culturally different characters can interact and apply intercultural skills.